PENGARUH TERAPI HYPNOPUNTURBREASTFEEDING DAN AIR SEDUHAN DAUN KELOR TERHADAP PRODUKSI ASI - Galih Setia Adi; Saelan Saelan (Universitas Muhammadiyah Semarang, 2018)
Exclusive breastfeeding is conducted since a new baby was born. Currently, the coverage of exclusive breastfeeding for babies are in aged 0-6 months, in Indonesia there are 19 provinces whose the coverage is above the national average (54.3%). this number cannot reach 100%, therefore it is necessary to increase the coverage rate of breastfeeding in babies 0-6 months. These data prove that many mothers do not give their breast milk. This is due to several things such as; the breast milk does not coming out at the beginning of a baby's birth, a family which does not support the mother in breastfeeding, the jobs which make difficult to breastfeed. The research aimed to identify the effect of hypnopunturbreastfeeding therapy and Moringa leaves steeping water on breast milk production in Sukoharjo. The research design used pre and post test control group in pure experimental research. The bivariate analysis used the Paired sample t-test. The results showed the differences in the giving of brest care therapy and water from Moringa leaves steeping water (control group) and in the post giving hypnopunkturbresfeeding, and the Moringa leaves steeping water. It can be seen from the sig value 0.000 which smaller than 0.005. Keywords: breast milk production, Akupuntur, Hypnobrestfeeding, Hypnopunturbreastfeeding, Moringa leaves steeping water